1999
DOI: 10.1007/pl00005377
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid CB1 receptor-mediated inhibition of NMDA- and kainate-stimulated noradrenaline and dopamine release in the brain

Abstract: Guinea-pig hippocampal slices preincubated with [3H]noradrenaline were superfused with medium containing desipramine and rauwolscine and rat striatal slices preincubated with [3H]dopamine were superfused with medium containing nomifensine; the effect of cannabinoid receptor ligands on tritium overflow stimulated by NMDA or kainate was examined. Furthermore, the affinity of the drugs for cannabinoid CB1 receptors was determined in rat brain cortex membranes using [3H]SR 141716. In guinea-pig hippocampal slices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(42 citation statements)
references
References 16 publications
1
40
0
1
Order By: Relevance
“…It is widely accepted that schizophrenia is associated with increased mesolimbic and decreased prefrontal dopaminergic activity [68], with the former mostly related to positive and the latter to negative symptoms [69][70]. Animal studies suggest that activation of cannabinoid CB1 receptors result in improved fronto-cortical function, and in either improved or worsened limbic dopaminergic function with cannabinoid receptor activation [71][72][73]. Hence, negative symptoms are more likely to be improved by cannabinoid use, whereas the effect on positive symptoms should be more controversial and unpredictable.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that schizophrenia is associated with increased mesolimbic and decreased prefrontal dopaminergic activity [68], with the former mostly related to positive and the latter to negative symptoms [69][70]. Animal studies suggest that activation of cannabinoid CB1 receptors result in improved fronto-cortical function, and in either improved or worsened limbic dopaminergic function with cannabinoid receptor activation [71][72][73]. Hence, negative symptoms are more likely to be improved by cannabinoid use, whereas the effect on positive symptoms should be more controversial and unpredictable.…”
Section: Discussionmentioning
confidence: 99%
“…NMDA is considered to have the stimulatory effects on dopamine release from brains of the rat and guinea pig (Kathmann et al, 1999;Whitehead et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…*P<0.05, compared with the corresponding control (not shown). From Kathmann et al (2001a), Kurz et al (2008), Nakazi et al (2000), Schlicker et al (1996Schlicker et al ( , 1997Schlicker et al ( , 2003, Schultheiss et al (2005) and unpublished data brain regions of the guinea pig (Kathmann et al 1999;Schlicker et al 1997). A facilitating effect of rimonabant was also found in the rat medial prefrontal cortex and nucleus accumbens (Tzavara et al 2003).…”
Section: Effects On Transmitter Releasementioning
confidence: 92%
“…Whereas in vitro studies in the rat striatum showed rimonabant-sensitive inhibitory effects of exogenous cannabinoids (Cadogan et al 1997;Kathmann et al 1999), in vivo studies in the same tissue reported stimulatory effects (Malone and Taylor 1999). The cannabinoid receptors in the latter model may be located on GABAergic interneurones synapsing with the dopaminergic perikarya.…”
Section: Effects On Transmitter Releasementioning
confidence: 99%
See 1 more Smart Citation